2018
DOI: 10.1115/1.4040421
|View full text |Cite
|
Sign up to set email alerts
|

Elastic Interaction in Bolted Flange Joints: An Analytical Model to Predict and Optimize Bolt Load

Abstract: Bolted flange joints are widely used in the nuclear power plants and other industrial complexes. During their assembly, it is extremely difficult to achieve the target bolt preload and tightening uniformity due to elastic interaction and criss-cross talks. In addition to the severe service loadings, the initial bolt load scatter increases the risk of leakage failure. The objective of this paper is to present an analytical model to predict the bolt tension change due to elastic interaction during the sequence o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 14 publications
0
7
0
Order By: Relevance
“…Liao et al [16,17] established a general dynamic model of bolted lap structure and a dynamic model of bolted lap structure with viscoelastic layer, and analyzed the influence of Coulomb friction and excitation level on the harmonic response of the system. Zhu et al [18,19] put forward an analytical model for evaluating the elastic interaction of bolt flange contact caused by the tightening process, and an analytical model for the change of bolt tensile load caused by the elastic combination interaction. Farhad et al [20] used the combination of linear translational spring, linear and nonlinear torsional spring and linear torsional damper to establish the model of bolt overlap interface, and used harmonic balance method and numerical simulation to analytically solve the coupled nonlinear equations.…”
Section: Introductionmentioning
confidence: 99%
“…Liao et al [16,17] established a general dynamic model of bolted lap structure and a dynamic model of bolted lap structure with viscoelastic layer, and analyzed the influence of Coulomb friction and excitation level on the harmonic response of the system. Zhu et al [18,19] put forward an analytical model for evaluating the elastic interaction of bolt flange contact caused by the tightening process, and an analytical model for the change of bolt tensile load caused by the elastic combination interaction. Farhad et al [20] used the combination of linear translational spring, linear and nonlinear torsional spring and linear torsional damper to establish the model of bolt overlap interface, and used harmonic balance method and numerical simulation to analytically solve the coupled nonlinear equations.…”
Section: Introductionmentioning
confidence: 99%
“…This is considered to be a problem, because the axial force of bolts in bolted joints formed from a metallic material cannot be uniform, since variations in axial force due to these elastic interactions are unavoidable. Analytical and experimental studies on tightening sequences have tried to minimize variations in the mechanism of the elastic interactions and in the axial force [15][16][17][18][19][20][21][22][23][24][25]. However, research into elastic interactions in bolted joints of wooden structures has not been found, so it is necessary to proceed with basic research on the implementation of the above-mentioned wood friction connectors in actual buildings.…”
Section: Introductionmentioning
confidence: 99%
“…Koves (1996) provided an analytical method for analyzing the behavior of bolted flange joints subjected to external loads. Other studies were conducted to enrich the research by including the three methods: experimental investigations, analytical modeling, and numerical analysis (Bouzid, Chaaban & Bazergui, 1995;Mallard, Landry & Birembaut, 2002;Bouzid & Nechache, 2005;Zhu, Bouzid, Hong & Zhang, 2018). This triangularization method of validation is often used to support the general findings.…”
Section: Introductionmentioning
confidence: 99%